A review paper on friction stir welding process. (2021) - Singh, Rudra Pratap; Dubey, Somil; Singh, Aman; Kumar, Subodh
Abstract: Friction stir welding is a solid state joining process that welds two or more similar or dissimilar materials having different melting points through a blend of heat created by friction and mechanical mixing of the materials in the locale of the joint. Different alloys having elements like aluminium, magnesium etc and hard materials like steels are generally welded by this method. These materials being light in weight are frequently used in transport and other such industries, where light weight materials having good mechanical properties are preferred. If the joining of these materials is done by any fusion welding techniques, the mechanical properties of the welds are reduced. In friction stir welding the mechanical properties of the materials to be joined are not reduced as welding takes place due to only the forging effect and no melting of materials takes place. This work contains the review of some important research papers on friction stir welding for similar or dissimilar materials. The papers for investigation in this work were considered since the invention of the friction stir welding process in 1991 with filing of a patent to till date and some important of them were selected for our work. The process parameters affecting the properties of welded products, applications and suggestions of the researchers were discussed in this work.